2005
DOI: 10.1186/1740-3391-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of litter separation on 24-hour rhythmicity of plasma prolactin, follicle-stimulating hormone and luteinizing hormone levels in lactating rabbit does

Abstract: Background: This work describes the effect of a 48-h litter separation on 24-h patterns of plasma prolactin, FSH and LH concentration in female lactating rabbits kept under a 16:8 light-dark photoperiod (lights on at 0800 h).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This behavior in morphometric dynamics of the ovary in relation to the color of the vulva can signal the effect that the weaning stimulus has and the different way in which does respond depending if they are primiparous or multiparous. Furthermore, the intense red of the vulva of the second and third parturition females suggest that they were receptive to males, as shown in previous studies (Díaz et al;Cano et al, 2005;Ola & Oyegbade, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…This behavior in morphometric dynamics of the ovary in relation to the color of the vulva can signal the effect that the weaning stimulus has and the different way in which does respond depending if they are primiparous or multiparous. Furthermore, the intense red of the vulva of the second and third parturition females suggest that they were receptive to males, as shown in previous studies (Díaz et al;Cano et al, 2005;Ola & Oyegbade, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Despite the short duration of each nursing bout, the altricial rabbit pups (which are blind for the first 10 days of life) can locate the mother's nipples and suckle milk due to the perception of an olfactory signal that is emitted from the mother's ventrum. In a series of studies we demonstrated that (a) Both in control and in does separated from their litter, plasma level of prolactin changed in a similar way throughout the day showing two maxima, at 05:00-09:00 h and at 17:00-21:00 h, respectively, litter separation significantly augmenting FSH and LH release and disrupting their 24-h rhythmicity in the mother [181]. (b) separation of newborn pups from their mother augmented circulating gonadotropin and PRL levels and disrupted 24-h rhythmicity of their release in pups and to a similar way in both sexes [181][182][183][184].…”
Section: Social Isolationmentioning
confidence: 92%
“…Nursing does are affected by a drop in prolactin levels, which may promote the progression of follicular waves and strong steroidogenesis activity, resulting in an increase in the concentration of estradiol-17beta (Ubilla et al, 2000a). By regulating the release of FSH and LH to the increased reaction of the ovulatory response to mating, the litter separation is a proactive strategy to promote ovarian activity (Cano et al, 2005a). The lack of suckling incidents in doe-litter separation may be due to the stimulating effects of ovarian activity, which raises the blood level of estradiol-17beta in does to improve receptivity and fertility.…”
Section: Influence Of Separating Rabbit's Offspring On Doe Blood and ...mentioning
confidence: 99%
“…The authors came to the conclusion that the doe-litter separation group's productivity increased by 35.4-44.2 percent. By altering the secretion of FSH and LH to be connected with the increased impulse of the ovulatory response to mating or by causing the AI process in does to separate from their offspring, Cano et al (2005a) discovered that litter separation is an active strategy to encourage ovarian activity before AI. Young rabbits being taken away from their mothers may put the does under stress and cause a lot of reactive oxygen species to be produced (ROS).…”
Section: Introductionmentioning
confidence: 99%